Mapping students’ performance in English reading literacy using the Rasch Measurement Model - Badrasawi, Kamal J (2012)
Monitoring learners’ performance in learning areas over time and across grade levels is essential to ensure that they are improving and achieving expected levels. In the Malaysian context, the monitoring and evaluation of students’ learning and achievement are conducted primarily through national standardized examinations such as the PMR (Penilaian Menengah Rendah/Lower Secondary Examination) and SPM (Sijil Pelajaran Malaysia/Malaysian Certificate of Examination).Though information gained from these examinations is useful, it is limited to students’ learning at particular levels of schooling. These examinations are also norm-referenced, making it impossible to determine the skills and knowledge that have been and have not been acquired. This paper highlights the utility of the Rasch Measurement Model (RMM) in the monitoring students’ performance across grade levels in the context of English reading literacy, and mapping students’ learning progress. A sample of 944 Form 1, 2, and 3 students was selected from eleven national-type secondary schools in two states in Malaysia. A test of English reading ability, comprising of 60 items, was used. RMM was used to produce person-maps and item-skill maps to clearly indicate what students have achieved and what has yet to be achieved. The results indicated that students differed in their performance across grade levels with lower levels showing higher achievement. The findings indicate the need for monitoring students’ progress over time and the use of a robust measurement model.